The Technological Research Outcomes of Boiled Sausages Fortified with Sea Buckthorn Peels - Bukyei, Erkigul; Baasanjargal, Buyanchimeg; Tumurba, Enkhbat atar; Ragchaa, Altanzul; Ganbold, Solongo (Department of Technology of Agricultural product (THP) Jambi University, 2023)
The article presents the evaluation of dried peels from sea-buckthorn fruit pomace obtained after juice production in Tes Sum, Uvs province, and its use in producing boiled-sausages. The boiled-sausages were enriched with four different sea buckthorn peel amounts: 0.2%, 0.3%, 0.4%, and 0.5%. According to the experimental research, compared to the reference, the amount of oil increased by 1.9%, fiber by 0.4%, flavonoids by 0.2mg%, calcium and magnesium by 2mg%, and iron by 0.2% in boiled sausages that were enriched with 0.4% sea buckthorn peels. Moreover, the moisture and nitrite content decreased by 3.3% and 2.2mg%, respectively.